Development of Virtual Painting Method using OpenCV Library with Finger Gesture on Online Learning Platform - Ramadhan, Glenn; Wiratama, Jansen; Permana, Angga Aditya (Jurnal Informatika, 2022)
With the pandemic situation that has occurred for the last two years to date, educators and students carry out many learning activities online. Learning activities are carried out using virtual meeting media, the concept of meetings and discussion processes that are carried out virtually with existing digital communication devices. From the problems, it was found that students were likelier to be less active when learning theory than practice, which made it difficult for educators to find various media that would be given to students to support online learning activities to be more interactive. This study discusses the creation of a system that can be a medium for delivering helpful material to improve the quality of interaction between educators and students. A virtual painter is one of the media to support the online interactive learning process, where educators can complete the material presented with a clearer picture that educators provide to students. Virtual painters are used to tracking finger pattern movements where the user moves his hand as needed, namely drawing and release, which educators can use to deliver more interactive material to students in theoretical and practical learning. The system design method used in building the virtual painting is Rapid Application Development (RAD) which is carried out through 8 stages, starting from Requirements Analysis to Operation and Maintenance. Next, the diagram design uses UML notation and the phyton with OpenCV coding process. After the virtual painter had been made, an evaluation was conducted and resulted in a positive impression of all six scales: attractiveness, efficiency, clarity, precision, stimulation, and novelty.